1996
DOI: 10.1016/s0035-9203(96)90121-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of deworming on indicators of school performance in Guatemala

Abstract: Intestinal helminths are among the most common infections in school-age children. Of 246 children, aged 7-12 years, attending school in rural Guatemala, 91% carried Ascaris lumbricoides and 82% carried Trichuris trichiura. These children were randomly assigned to receive either albendazole or placebo at 0 and 12 weeks in a 'double-blind' study of the effects of deworming on indicators of school performance. Albendazole successfully rid the children of Ascaris but it was less effective against Trichuris. The ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 9 publications
2
71
1
2
Order By: Relevance
“…While previous studies have shown improvement in school achievement and cognitive tests following de-worming programmes, 3,39 de-worming 7-12-year-old rural Guatemalan children with high parasite loads failed to affect their school performance. 42 Albendazole was found in that study to be successful in treating Ascaris infection but to be less effective against Trichuris, similar to our results.…”
Section: Discussionsupporting
confidence: 91%
“…While previous studies have shown improvement in school achievement and cognitive tests following de-worming programmes, 3,39 de-worming 7-12-year-old rural Guatemalan children with high parasite loads failed to affect their school performance. 42 Albendazole was found in that study to be successful in treating Ascaris infection but to be less effective against Trichuris, similar to our results.…”
Section: Discussionsupporting
confidence: 91%
“…In Simeon, Grantham-McGregor, Callender, and Wong's (1995, A) experimental study in Jamaica, treatment of children with whipworm interacted with low height-for-age and high worm burden to produce better spelling scores; treated children with stunted growth also had better attendance. However, the study of Watkins et al (1996a, A) among children with both roundworm and whipworm found no effect of deworming on reading, vocabulary, and attendance scores and no interactions of treatment with worm load.…”
Section: Results By Psychological Domainmentioning
confidence: 94%
“…Of these, five (reported in seven reports 18 24 30 33 35 – 37) reported cognitive outcomes, while two reports from one study included both cognitive and growth outcomes 45 46. Two trials that reported effects on growth or nutrition compared the effectiveness of different drug dosages or drugs and are not included in this review 48 49.…”
Section: Methodsmentioning
confidence: 99%